Biochemical profile and oocyte quality of primiparous Bos indicus cows submitted to a timed artificial insemination protocol - Bottino, Miguel Pizzolante; Carvalho, Laís Reis; Orlandi, Raphael Evangelista; Santos, Ana Paula Castro; Simões, Luiz Manoel Souza; Perecin, Felipe; Andrade, Gabriella Mamede; Nogueira, Guilherme de Paula; Maioli, Marcos Antônio [UNESP]; Sales, José Nélio de Sousa (Elsevier, 2024)
The objective of this study was to verify the causes of the lower response of primiparous Bos indicus cows to the ovulation synchronization protocol. Two experiments were performed to evaluate the biochemical profile, oocyte and follicular cell quality (Experiment 1) and pregnancy (Experiment 2). In Experiment 1, suckled primiparous (n = 24) and multiparous cows (n = 24) were submitted to ovum pick up (OPU). On Day 0 (D0), all cows received 2 mg of estradiol benzoate (EB) and an intravaginal progesterone insert (P4). Five days (D5) after the first hormonal administration (EB + P4), all follicles larger than 3 mm were counted on each ovary, and ovum pick-up (OPU) was performed. On day 12 (D12), the intravaginal progesterone insert was removed, and measurement and aspiration of the largest follicle were performed. Blood samples were collected on D5 and D12 to evaluate the concentrations of glucose, cholesterol, NEFA, IGF-1 and insulin. In Experiment 2, suckled primiparous (n = 50) and multiparous (n = 50) cows were subjected to an ovulation synchronization protocol based on E2/P4 (D0: 2 mg EB plus P4 intravaginal insert; D8: 500 μg of cloprostenol, 1 mg cypionate estradiol and 300UI of eCG; D10: artificial insemination). In addition, blood samples were collected on D10 for evaluation of the same hormones and metabolites described in Experiment 1. In all studies, calves remained with the cows during the experimental period. In experiment 1, the number of oocytes grade 1 (P = 0.83), grade 2 (P = 0.23) and grade 3 (P = 0.51), total number of retrieved oocytes (P = 0.14), oocyte quality index (P = 0.93) and total viable oocytes (P = 0.38) did not differ between primiparous and multiparous cows. The number of follicles at the time of follicular aspiration (20.7 ± 1.5 vs. 18.0 ± 1.9; P = 0.05) and the diameter of the largest follicle on D12 (13.5 ± 0.6 vs. 11.4 ± 0.6; P = 0.04) were greater in multiparous cows, and the number of degenerated oocytes was greater in primiparous cows (1.9 ± 0.7 vs. 1.2 ± 0.3; P = 0.05). On D5, the concentrations of IGF-1 (P = 0.47), insulin (P = 0.08), total cholesterol (P = 0.47), NEFA (P = 0.77) and glucose (P = 0.55) in the blood and IGF-1 (P = 0.97) and insulin (P = 0.11) in the follicular fluid did not differ between parity groups. On D12, there was no difference in the concentrations of IGF-1 (P = 0.26), total cholesterol (P = 0.32), NEFAs (P = 0.31) and glucose (P = 0.93) in the blood between primiparous and multiparous cows, however, the serum insulin concentration (P = 0.04) was higher in primiparous cows. There was no correlation between serum and follicular fluid insulin concentrations (r = 0.17; P = 0.31), however, there was a low correlation between serum and follicular fluid IGF-1 concentrations (r = 0.47; P = 0.002). Quantification of transcripts did not differ between parity groups. In experiment 2, concentrations of NEFA (P = 0.12) and insulin (P = 0.16) in the blood and P/AI (P = 0.93) did not differ between parity [60 % (30/50) primiparous vs. 60 % (30/50) multiparous]. In contrast, blood concentrations of IGF-1 (P = 0.0001), total cholesterol (P = 0.005) and glucose (P = 0.01) were greater in primiparous cows. It was concluded that the oocyte quality and expression of the genes evaluated in the granulosa cells were not different between primiparous and multiparous cows. Unexpectedly, the pregnancy rate did not differ between parity. Nevertheless, the blood concentrations of IGF-1, total cholesterol and glucose were greater in primiparous cows.
Keywords: Fertility; Parity; TAI; Zebu